2016
DOI: 10.12688/f1000research.8457.1
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of diabetes mellitus and impaired glucose tolerance in liver cancer patients: A hospital based study of 4610 patients with benign tumors or specific cancers

Abstract: Objective: The prevalence of diabetes mellitus (DM), impaired glucose tolerance (IGT) and impaired fasting glucose (IFG) were hypothesised to be different among different tumor patients. This study aimed to study the association between the prevalence of DM, IGT and IFG and liver cancer, colorectal cancer, breast cancer, cervical cancer, nasopharyngeal cancer and benign tumor. Methods:  A hospital based retrospective study was conducted on 4610 patients admitted to the Internal Medical Department of the Affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(19 reference statements)
0
2
1
Order By: Relevance
“…Meta-analysis of three studies conducted in Asia also showed an inverse association between DM and NPC (OR =0.62, 95% CI: 0.39–0.97, P =0.04) ( Figure 2 ). 15 17 The above results suggest that DM appears to be correlated with a trend toward decreased NPC risk, which is quite different from the finding that DM is positively associated with an increased risk of most other cancers.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Meta-analysis of three studies conducted in Asia also showed an inverse association between DM and NPC (OR =0.62, 95% CI: 0.39–0.97, P =0.04) ( Figure 2 ). 15 17 The above results suggest that DM appears to be correlated with a trend toward decreased NPC risk, which is quite different from the finding that DM is positively associated with an increased risk of most other cancers.…”
Section: Resultscontrasting
confidence: 80%
“…The lack of comparability between groups was found in two studies. 15 , 17 The study of Tseng et al did not exclude potential cancer patients in the control group at the initial time of identifying patients. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Findings of previous studies have pointed in the same direction. 21,27,31,32 In contrast to earlier studies, our results provide a systematic overview of the prevalence of preDM and DM for various cancer types. 33 For most of these cancer types, the prevalence of preDM has never been reported.…”
Section: Original Research Cancer and Diabetesmentioning
confidence: 72%